2014
DOI: 10.1007/s10803-013-2031-4
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Reduced Grouping Interference in Children with ASD: Evidence from a Multiple Object Tracking Task

Abstract: This study was inspired by the more locally oriented processing style in autism spectrum disorders (ASD). A modified multiple object tracking (MOT) task was administered to a group of children with and without ASD. Participants not only had to distinguish moving targets from distracters, but they also had to track targets when they were visually grouped to distracters, a manipulation which has a detrimental effect on tracking performance in adults. MOT performance in the ASD group was also affected by grouping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 52 publications
(68 reference statements)
2
33
2
1
Order By: Relevance
“…Similar to Evers et al (2014), three average scores (one per condition) and one overall interference score were computed for each participant. The average scores refer to the average number of correctly identified targets (possible range 0-4) across trials within a particular condition.…”
Section: Data-analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Similar to Evers et al (2014), three average scores (one per condition) and one overall interference score were computed for each participant. The average scores refer to the average number of correctly identified targets (possible range 0-4) across trials within a particular condition.…”
Section: Data-analysismentioning
confidence: 99%
“…Previously, Scholl et al (2001) have found stronger detrimental effect for object-based grouping than for connection-based grouping, and Evers et al (2014) have found diminished grouping interference for connection-based grouping in children with ASD. Therefore, we predicted a large differential effect of grouping interference, i.e., stronger grouping interference in TD children than was shown for connection-based grouping (in line with Scholl et al), and subtle grouping interference for children with ASD (in line with Evers et al).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations